Simple circuits - Fong, Angelina (Henry Stewart Talks, 2024)
Neuronal activity, Neuronal networks, Excitatory neurons, Inhibitory neurons, Advanced simple circuits, Feedback loops, Reflex, Convergent and divergent circuits